Dual Role of Hydrogen Peroxide in Arabidopsis Guard Cells in Response to Sulfur Dioxide. (30th September 2014) - Yi, Huilan; Liu, Xin; Yi, Min; Chen, Gang
Abstract : Sulfur dioxide (SO2 ) is a major air pollutant and has significant impacts on plant physiology. Plant can adapt to SO2 stress by controlling stomatal movement, gene expression, and metabolic changes. Here we show clear evidences that SO2 -triggered hydrogen peroxide (H2 O2 ) production mediated stomatal closure and cell death in Arabidopsis leaves. High levels of SO2 caused irreversible stomatal closure and decline in guard cell viability, but low levels of SO2 caused reversible stomatal closure. Exogenous antioxidants ascorbic acid (AsA) and catalase (CAT) or Ca 2+ antagonists EGTA and LaCl3 blocked SO2 -induced stomatal closure and decline in viability. AsA and CAT also blocked SO2 -induced H2 O2 and[ Ca 2 + ] cyt elevation. However, EGTA and LaCl3 inhibited SO2 -induced[ Ca 2 + ] cyt increase but did not suppress SO2 -induced H2 O2 elevation. These results indicate that H2 O2 elevation triggered stomatal closure and cell death via[ Ca 2 + ] cyt signaling in SO2 -stimulated Arabidopsis guard cells. NADPH oxidase inhibitor DPI blocked SO2 -induced cell death but not the stomatal closure triggered by low levels of SO2, indicating that NADPH oxidase-dependent H2 O2 production plays critical role in SO2 toxicity but is not necessary for SO2 -induced stomatal closure. Our results suggest that H2 O2 production and accumulation in SO2 -stimulated plants trigger plant adaptation and toxicity via reactive oxygen species mediating Ca 2+ signaling.